Design and fault tolerant analysis of five-phase permanent magnet synchronous motor - Ahmad Sofian Saari Saari; Dahaman Ishak (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a design of 15-slot/12-pole, five-phase, surface-mounted permanent magnet synchronous motor (PMSM).  The five-phase PMSM can be an attractive solution to few applications that demand fault tolerant capability such as in aerospace engineering and electric propulsion. The motor model is first investigated based on the implementation of analytical method. The analytical method derived from the subdomain model of the permanent magnet machine is initially applied to estimate the magnetic flux density distributions for the radial component Br and the tangential component Bt in the machine air gap. Other important motor characteristics such as phase back-EMF, line back-EMF, cogging torque and electromagnetic torque are also calculated. The analytically calculated results are then compared with the numerical method in a 2D finite element analysis. Additionally, the capability of this PMSM model against faulty conditions are further investigated. The results show that the analytical model of the 15-slot/12-pole, five-phase PMSM provides very accurate motor performance within acceptable error margin. For instance, the average electromagnetic torques, inclusive of the cogging torque, as computed by the analytical and numerical methods are 5.53Nm and 5.33Nm respectively, yielding an error of 3.6%. During faulty conditions, the PMSM can possibly continue to operate with lower output torque, about 60% to 80% of its rated torque, when one-phase or two phase windings are out of service.